2011
DOI: 10.1111/j.1468-5973.2010.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

The Legacy of the High Reliability Organization Project

Abstract: This article looks back over two decades of work pioneered by Todd LaPorte and colleagues, under the banner of High Reliability Theory (HRT). The article revisits the American roots of the Berkeley-based group and comments on its early and decisive fieldwork choices. It revisits some of the elements that emerged through the controversy around findings and implications of HRT. It discusses the legacy of HRT and the ethnographical impetus given to 'normal operations' studies. The use of ethnographic and sociolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 24 publications
2
37
0
2
Order By: Relevance
“…After excluding duplicate studies, the titles and abstracts were screened for 2724 records, and after all inclusion and exclusion criteria were applied 15 studies were included in the qualitative synthesis using the CASP tool ( Table 2). Of the 15 studies, seven studies [23,[36][37][38][39][40][41] were identified through hand searching of the reference lists of all studies [23,27,30,[36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After excluding duplicate studies, the titles and abstracts were screened for 2724 records, and after all inclusion and exclusion criteria were applied 15 studies were included in the qualitative synthesis using the CASP tool ( Table 2). Of the 15 studies, seven studies [23,[36][37][38][39][40][41] were identified through hand searching of the reference lists of all studies [23,27,30,[36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Other definitions [42,46,51] suggested HRO to be nearly error and accident-free. These similarities suggest there is a common understanding of HRO, but no unified definition is available for now.…”
Section: Definitions For Hromentioning
confidence: 99%
See 3 more Smart Citations